2011
DOI: 10.5588/ijtld.10.0759
|View full text |Cite
|
Sign up to set email alerts
|

Environmental tobacco smoke exposure increases Mycobacterium tuberculosis infection risk in children

Abstract: Exposure to ETS is associated with M. tuberculosis infection in children after adjustment for multiple variables, with a dose-response relationship between the degree of ETS exposure and risk of infection. Public health interventions to reduce exposure to tobacco smoke among children in high TB burden settings are urgently needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 0 publications
0
28
0
Order By: Relevance
“…3–7 It is known that exposure to IAP increases the risk of respiratory infection and asthma-related illnesses in children, with few studies assessing the role IAP plays in TB disease. 22,2931 Two studies have found an association between tuberculin skin test positivity and passive tobacco exposure; 30,31 however, this is one of the first studies to demonstrate a strong epidemiological link between exposure to IAP and pediatric TB disease. While this study was not powered to assess passive tobacco smoke exposure or biomass fuel exposure individually, tobacco exposure approached statistical significance, while biomass fuel exposure was highly independently associated with TB using the more stringent research definition of TB.…”
Section: Discussionmentioning
confidence: 92%
“…3–7 It is known that exposure to IAP increases the risk of respiratory infection and asthma-related illnesses in children, with few studies assessing the role IAP plays in TB disease. 22,2931 Two studies have found an association between tuberculin skin test positivity and passive tobacco exposure; 30,31 however, this is one of the first studies to demonstrate a strong epidemiological link between exposure to IAP and pediatric TB disease. While this study was not powered to assess passive tobacco smoke exposure or biomass fuel exposure individually, tobacco exposure approached statistical significance, while biomass fuel exposure was highly independently associated with TB using the more stringent research definition of TB.…”
Section: Discussionmentioning
confidence: 92%
“…Studies from high burden TB regions demonstrate an association between ETS exposure and development of TB disease in adults [52,53]. While the effects of tobacco smoking and exposure on TB have been well described in adults, there are fewer studies focusing on children.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have found individuals with latent TB infection (LTBI) are more likely to be smokers or exposed to second-hand smoke (SHS) ( Table 1). [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] The strength of the associations between LTBI and SHS 15,17,18,21 or direct CS 8,9,11,12,14,16,22,23 exposure is summarized in Figure 1a. There also appears to be an association between the degree of cigarette smoking-as measured by duration or intensity of smoking-and LTBI (Fig.…”
Section: Tb Infection With Cs Exposurementioning
confidence: 99%
“…Having ≥two smokers in a household is associated with positive TST. 18 Tijuana, Mexico (2012) Longitudinal study of 129 intravenous drug users.…”
Section: Shsmentioning
confidence: 99%